La traducción de marcadores discursivos (DM) inglés-español en los subtítulos de películas: un estudio de corpus - Rica-Peromingo, Juan-Pedro (The Journal of Specialised Translation, 2014)
This paper presents an initial analysis of the translation of discourse markers (DM) used in oral speech. This analysis is based on Biber et al. (1999, 2003)'s taxonomy on discourse functions in oral English and the theoretical framework based on various research fields: corpus linguistics, phraseology and audiovisual translation. This research is being carried out, on the one hand, due to the great variety of discourse functions found in the English language which require a careful translation and which are affected in many cases by the use of calques from English into Spanish subtitles. For such purpose an analysis of those DM most frequently used in English and their translations into Spanish will be presented, with the use of a sample from an own bilingual corpus (CORSUBIL, Corpus de Subtítulos Bilingües inglés-español) which is being compiled. The ultimate aim of this research will be the design of a bilingual taxonomy of DM in English and in Spanish. This taxonomy will allow researchers to investigate in the use of these fixed units in both languages.